Cytotoxicity of Calcium Silicate-Based Cements: Role of Bonding Time, Strategy, and Thickness in an In Vitro Model - Panahandeh, Narges; Torshabi, Maryam; Askian, Roja; Torabzadeh, Hassan; Asgary, Saeed (Iranian Endodontic Journal, 2025)
Introduction: This in vitro study assessed the effects of bonding application time (immediate vs. 24-hour delay) and strategy [self-etch (SE) vs. etch-and-rinse (ER)] on cytotoxicity of three calcium silicate-based cements [calcium-enriched mixture (CEM) cement, ProRoot mineral trioxide aggregate (MTA) and Biodentine] at 1mm and 2mm thicknesses. Materials and methods: Specimens (n=20 per group) were fabricated using CEM, MTA, and Biodentine. Scotchbond Universal was applied immediately or after 24 hours via SE or ER strategies. Cytotoxicity of cement extracts (100%, 50%, and 25% concentrations) on human gingival fibroblasts was evaluated using methyl thiazolyl tetrazolium (MTT) assay. Data were analyzed with four-way ANOVA and Tukey’s test (P≤0.05). Results: The biomaterials showed comparable cytotoxicity (P>0.05), with toxicity decreasing progressively at lower concentrations (25% <50%<100%). At 100% concentration, ER bonding significantly improved cell viability for CEM (P<0.05), while immediate bonding of 1-mm specimens increased cytotoxicity (P<0.05). Immediate SE bonding of 1-mm MTA and Biodentine specimens also resulted in higher cytotoxicity (P<0.05). At 50% concentration, SE strategy and 1-mm thickness increased cytotoxicity, with bonding time effects significant only in ER mode. No significant differences were observed at 25% concentration (P>0.05). Conclusion: Delayed bonding (24 hours), ER strategy, and ≥2-mm thickness minimize cytotoxicity of calcium silicate-based cements. Clinically, immediate permanent restoration after vital pulp therapy is viable when considering these parameters, eliminating the need for interim protective layers (e.g., glass ionomer bases).